2019
DOI: 10.1111/ceo.13506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined goniotomy and phacoemulsification on intraocular pressure in open‐angle glaucoma patients

Abstract: Importance Although goniotomy is known to be successful in treating congenital glaucoma, its effect in adult glaucoma patients remains unclear. Background To evaluate the efficacy and safety of goniotomy performed simultaneously with cataract surgery in treatment of open‐angle glaucoma (OAG). Design Retrospective comparative study. Participants A total of 76 patients with moderately controlled OAG (intraocular pressure [IOP] ≤ 21 mmHg using medications) undergoing cataract surgery. Methods Comparison of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The presence of posterior capsular opacification in some eyes is the reason for the measured CDVA at six months. A fundamental difference between our study and previous studies[ 20 22 24 ] was that we did phacoemulsification before goniotomy. Experimentally, we did direct gonioscopy before and after phaco alone surgery and recognized the angle is wider and more suitable for goniotomy after phacoemulsification and posterior chamber IOL implantation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The presence of posterior capsular opacification in some eyes is the reason for the measured CDVA at six months. A fundamental difference between our study and previous studies[ 20 22 24 ] was that we did phacoemulsification before goniotomy. Experimentally, we did direct gonioscopy before and after phaco alone surgery and recognized the angle is wider and more suitable for goniotomy after phacoemulsification and posterior chamber IOL implantation.…”
Section: Discussionmentioning
confidence: 77%
“…Kim et al . [ 24 ] in a study compared combined phaco and conventional needle goniotomy with phaco alone in OAG patients. Mean IOP and number of medications at 3, 6, and 12 months after the procedure was not different between groups while the drop of IOP was significantly higher in the combined surgery group at 3 (13.7% versus 6.3%), 6 (17.5% versus 8.6%), and 12 (17.0% versus 8.0%) months.…”
Section: Discussionmentioning
confidence: 99%
“…It could be done as a standalone surgery or combined with cataract surgery. 17 In this study, we compared phacoemulsi cation alone versus combined phaco-goniotomy in patients with cataract and POAG in terms of IOP control, the number of antiglaucoma medications, and safety pro le. We found a signi cant reduction of IOP in patients with moderate glaucoma who had combined phacogoniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the 3 surgeries decreased IOP and ocular hypotensive medications when compared with their own baseline, which is similar to other studies comparing IOP decrease and medication reduction. 17,20,21,[39][40][41][42][43] However, while this type of analysis within groups is simple and demonstrates the greatest effect on IOP lowering and medication burden, a comparison between groups is difficult because of preoperative and postoperative differences in IOP and ocular hypotensive medications. When we subdivided the groups based on the number of medications (1, 2, or 3+) the difference between group remained nonsignificant.…”
Section: Discussionmentioning
confidence: 99%